2010
DOI: 10.5367/te.2010.0008
|View full text |Cite
|
Sign up to set email alerts
|

Internal and Locational Factors Affecting Hotel Industry Efficiency: Evidence from Italian Business Corporations

Abstract: This paper investigates whether and how the competitive delay of the Italian hotel industry is influenced by the level of business corporation efficiency. A stochastic frontier production approach is proposed in which technical inefficiency is specified as a function of the internal and locational factors in a firm. The model is estimated on a balanced panel of tourism business corporations observed during 1998–2005. Estimates show that the competitive gap in the Italian accommodation system is not a result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…The variable Attractions is introduced to investigate the influence of hotel's location on its efficiency. Bernini and Guizzardi (2010) suggest that location is positively correlated with technical efficiency, especially for sun and beach destinations, as well as cities with renowned cultural importance. Thus, resources that may contribute to the attractiveness of a hotel's location need to be conserved (Gomezelj & Mihali c, 2008).…”
Section: Identification Of Efficiency Driversmentioning
confidence: 94%
See 1 more Smart Citation
“…The variable Attractions is introduced to investigate the influence of hotel's location on its efficiency. Bernini and Guizzardi (2010) suggest that location is positively correlated with technical efficiency, especially for sun and beach destinations, as well as cities with renowned cultural importance. Thus, resources that may contribute to the attractiveness of a hotel's location need to be conserved (Gomezelj & Mihali c, 2008).…”
Section: Identification Of Efficiency Driversmentioning
confidence: 94%
“…In the hotel industry, examples of contextual factors include hotel size , location (Barros, 2005a;Bernini & Guizzardi, 2010;Tundis et al, 2012), and type of ownership (Barros & Dieke, 2008), which are found to be strong determinants of hotel efficiency in many case studies. Other variables could also be pertinent, like star rating (Assaf & Cvelbar, 2010), used essentially to reflect quality of service, even though it is far from being a wholly satisfactory proxy for such an operational factor (Oliveira, Pedro, & Marques, 2013).…”
Section: Identification Of Efficiency Driversmentioning
confidence: 96%
“…The empirical literature on tourism firm efficiency has been dominated by a non-parametric approach-the data envelopment analysis (DEA) (e.g., Barros & Alves, 2004;Chiang, Tsai, & Wang, 2004). The main advantages of DEA compared to the standard econometric technique are that it 1) does not require any form of functional specification and 2) is able to handle multiple inputs and outputs readily in any (in)efficiency theoretical paradigm (Bernini & Guizzardi, 2010). Based on the input and output data from DEA, a Malmquist Index can be constructed to measure productivity change.…”
Section: The Structure-conduct-performance (Scp) Paradigmmentioning
confidence: 99%
“…George Assaf (2012) uses the stochastic frontier analysis and DEA to evaluate and compare the tourism operators and hotels in the Asia-Pacific region. Bernini and Guizzardi (2010) use the DEA to study the efficiency and competitiveness of the Italian hotel industry. Assaf, Barros, and Josiassen (2010) and other analysts use DEA to evaluate the operation efficiencies of the hotels in Taiwan (Chen, Hu, & Liao, 2010;Cheng, Lu, & Chung, 2010;Chiu, Ting, & Huang, 2010;Hsieh & Lin, 2010;Hsieh, Wang, Huang, & Chen, 2010;Hu, Shieh, & Huang, 2009;Huang, Chiu, Ting, & Lin, 2011;Shang, Wang, & Hung, 2010;Ting & Huang, 2012;Wu, Liang, & Song, 2010;Wu & Song, 2011;Yu & Lee, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%